Exploring Barriers and Solutions of Online Learning During the Covid-19 Pandemic By Vocational School Teachers - Fahmalatif, Farida; PURWANTO, AGUS; Siswanto, Edy; Ardiyanto, Jeffri (AGUSPATI Research Institute, 2021)
This study aims to determine the problems experienced by teachers during Covid-19 pandemic in which teachers must conduct online learning. This research is a descriptive study using the online survey method. The data was collected using online questionnaires to 120 respondents of teacher vocational schools. It was found that 98% of the vocational schools teachers respondents have conducted online learning during the Covid-19 pandemic, and 1 teacher did not use online model. The information obtained is that 100% of the teacher is doing online learning model (in the network). More than 9 medias used by vocational schools teachers in Bantul district during the pandemic were offered namely WhatsApps, WhatsApp Web, Google Classroom, Google Group, TeamLink, Microsoft Teams, Kaizala Microsoft, Zoom Meeting & Webinar, Youtube, Google Hangouts, and others. 100% of teachers or as many as 87 teachers are learning with WhatsApps application as the first choice. Furthermore, 16% of teachers use some application supporters of WhatsApp. Google Class is the second option. The third option is Google form as much as 14% or 8 teachers. The use of Google Form is for students' worksheets. The fourth choice is YouTube with as many as 9% or 5 teachers. Short videos related to the material being taught in 10-24 minutes. The fifth application is the Zoom Cloud Meeting for only 4% or6 teachers who chose this platform.